2001
DOI: 10.1002/ffj.1016
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition of Cinnamomum zeylanicum Blume leaves from Little Andaman, India

Abstract: The leaf oil of Cinnamomum zeylanicum Blume grown in Little Andaman was analysed by GC and GC-MS. Forty-seven constituents, representing 99.96% of the oil, were identified. The main constituents of the oil were eugenol (76.60%), linalool (8.5%) and piperitone (3.31%). The composition of the oil is comparable to cinnamon leaf oil produced in Bangalore and Hyderabad (south India) in terms of eugenol and linalool contents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 9 publications
3
24
1
Order By: Relevance
“…GC‐MS analysis showed that the major component of cinnamon leaf oil used in this study was eugenol, which was 84·5% of the total oil composition. This is similar to findings in the current literature (Mallavarapu et al ; Paranagama et al ; Raina et al ; Jayawardena and Smith ). In contrast, the major component of the cinnamon bark EO used in this study was Σ‐cinnamaldehyde at 85·3% of the total composition.…”
Section: Discussionsupporting
confidence: 93%
“…GC‐MS analysis showed that the major component of cinnamon leaf oil used in this study was eugenol, which was 84·5% of the total oil composition. This is similar to findings in the current literature (Mallavarapu et al ; Paranagama et al ; Raina et al ; Jayawardena and Smith ). In contrast, the major component of the cinnamon bark EO used in this study was Σ‐cinnamaldehyde at 85·3% of the total composition.…”
Section: Discussionsupporting
confidence: 93%
“…Raina et al (2001) and Prabuseenivasan et al (2006) found that cinnamaldehyde is the major component of the EO of C. zeylanicum. Raina et al (2001) and Vangalapati et al (2012) showed that this essential oil contains alpha copaene, Caryophylleneoxide, Di-n-octylphthalate and Bornyl cinnamate.…”
Section: Discussionmentioning
confidence: 99%
“…They have reported that eugenol is the major volatile compound (87.3%) and no trans-cinnamaldehyde is detected. Raina, Srivastava, Aggraval, Ramesh and Kumar (2001) have suggested eugenol (76.6%), linalool (8.5%) and pipertone (3.3%) as three major components of C. zeylanicum leaf oil. These results are different to our results obtained in this work.…”
Section: Identification Of Volatile Compounds In Essential Oilsmentioning
confidence: 99%